THE USE OF LESSON PLAN GUIDELINES BASED ON LEARNING MODELS TO FACILITATE VOCATIONAL TEACHERS TO DEVELOP COMPETENCY INDICATORS - suherman, amay; Komaro, Mumu (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
The gaps in student competence with industrial demands make graduates of vocational high schools not widely absorbed in the workforce. This study aims to enhance the ability of vocational teachers in compiling indicators of competency using a lesson plan guidelines based on a learning models. The study was conducted with a qualitative approach through the action research method. The participants involved in this study came from three vocational schools in Bandung, West Java, Indonesia. The informants involved in this study were six male teachers, having more than five years of work experience and teaching productive subjects. Data collection by Focus Group Discussion (FGD) to obtain general information and individual interviews to obtain more specific data. After the data is documented and evaluated, then proceed with guiding respondents to develop indicators of competence using the lesson plan guidelines. The results of the research are expected to increase the ability of teachers to compile indicators of competence through the guidance of the lesson plan based on a learning models. So that this research will have implications for the achievement of student competencies in accordance with the demands of the job/industry.